2012
DOI: 10.1007/s10549-012-2257-4
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to polychlorinated biphenyl (PCB) congeners measured shortly after giving birth and subsequent risk of maternal breast cancer before age 50

Abstract: Discrete windows of susceptibility to toxicants have been identified for the breast, including in utero, puberty, pregnancy, and postpartum. We tested the hypothesis that polychlorinated biphenyls (PCBs) measured during the early postpartum predict increased risk of maternal breast cancer diagnosed before age 50. We analyzed archived early postpartum serum samples collected from 1959 to 1967, an average of 17 years before diagnosis (mean diagnosis age 43 years) for 16 PCB congeners in a nested case–control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 27 publications
(50 reference statements)
0
43
0
Order By: Relevance
“…The Child Health and Development Studies (CHDS) have found that women who have high levels of polychlorinated biphenyls (PCBs) in their blood immediately after giving birth have a tripled risk of developing breast cancer nearly two decades later 7 . The pesticide DDT has an even greater effect 8 .…”
Section: A Question Of Quantitymentioning
confidence: 99%
“…The Child Health and Development Studies (CHDS) have found that women who have high levels of polychlorinated biphenyls (PCBs) in their blood immediately after giving birth have a tripled risk of developing breast cancer nearly two decades later 7 . The pesticide DDT has an even greater effect 8 .…”
Section: A Question Of Quantitymentioning
confidence: 99%
“…Some epidemiological evidence has been published on the link between human exposure to POPs and the risk of certain types of cancer (Boada et al, 2012;Brauner et al, 2012b;Cohn et al, 2012;Cohn et al, 2007;McGlynn et al, 2008;Recio-Vega et al, 2011;Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic evidence for an increase in breast cancer risk is limited, perhaps because most of the occupational studies of heavy metals have been done in men. Both lead and cadmium have estrogenic properties (24) and have been associated with breast cancer in human epidemiologic studies (19,87). Lead exposure has been associated with later pubertal onset or menarche in several studies (34,123,157).…”
Section: Metalsmentioning
confidence: 99%